2020
DOI: 10.1097/bpo.0000000000001112
|View full text |Cite
|
Sign up to set email alerts
|

Collateral Ligament Knee Injuries in Pediatric and Adolescent Athletes

Abstract: Level IV-retrospective case series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 28 publications
0
15
0
3
Order By: Relevance
“…Return to multidirectional sport was achieved at 4 months which is longer than the median recovery period described in the series by Kramer et al despite being within the observed range,11 however, Kramer et al included MCL injuries in this outcome measure. Return to sport is governed by many factors including psychological factors including patient’s motivation and does not necessarily correlate with injury grade which may explain the discrepancy in previous outcome reports.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Return to multidirectional sport was achieved at 4 months which is longer than the median recovery period described in the series by Kramer et al despite being within the observed range,11 however, Kramer et al included MCL injuries in this outcome measure. Return to sport is governed by many factors including psychological factors including patient’s motivation and does not necessarily correlate with injury grade which may explain the discrepancy in previous outcome reports.…”
Section: Discussionmentioning
confidence: 71%
“…A recently published retrospective case series from the USA assessing outcomes of ‘cruciate-normal’ collateral ligament injuries in children and adolescents (average age 13.8 years) over an 8-year period identified a total of 51 injuries, of which only six were isolated LCL injuries and only two involving a rupture of the distal ligament like  our case 11. Kramer et al reported a return to sport of median 2.2 months for all injury types (MCL, LCL, PLC and avulsions) with 95% of players returning to sport by 4 months but unfortunately no subgroup analysis to report the duration of rehab for LCL injuries specifically.…”
Section: Discussionmentioning
confidence: 76%
“…EL método de valoración en resonancia magnética que se utilizó fue de acuerdo a la clasificación internacional de lesiones de ligamento medial 10 (Tabla 1).…”
Section: Materials Y Métodosunclassified
“…xiert [8]. Rein ligamentäre Verletzungen der Seitenbänder werden in der Regel konservativ behandelt [32].…”
Section: Operative Versorgungunclassified